"How to Recognize if Your Child Is Seriously Ill" During COVID-19 Lockdown: An Evaluation of Parents' Confidence and Health-Seeking Behaviors - Emma Lim; Emma Lim; Ravi D. Mistry; Alexandra Battersby; Alexandra Battersby; Kerry Dockerty; Aaron Koshy; Michelle N. Chopra; Matthew C. Carey; Jos M. Latour; Jos M. Latour (Frontiers Media S.A., 2020)
Background: Parents' health-seeking behaviors has changed during the COVID-19 pandemic. Providing parents with guidance in decision making might improve their confidence to seek timely advice when a child becomes ill. The aim of this study was to evaluate the "How to recognize if your child is seriously ill" leaflet on parents' confidence, health-seeking behaviors, and usefulness during the COVID-19 lockdown.Method: A nine-item survey, codesigned with parent advisors, was used to measure confidence and health-seeking behavior. Social media was used for data collection in a 6-week period (April-June 2020) during COVID-19 lockdown in the United Kingdom. Categorical data were analyzed as frequencies, and inductive content analysis was performed with the qualitative data.Results: In total, 171 parents responded. Most parents (n = 160, 93.6%) found the leaflet helpful. The leaflet increased the confidence among 116 parents (67.8%) to recognize if their child is ill, and 156 (91.2%) parents had a better understanding of when and where to seek help. Thirty-three (19.2%) parents used the leaflet, while their child was unwell during COVID-19 lockdown, and in 14 (42%) cases, the leaflet resulted in changing health-seeking behavior for that episode. Twelve of these parents decided to seek medical consultation when they had not planned to before. Content analysis revealed three categories. (1) Knowledge-parents found the leaflet an objective source to validate their concerns. (2) Usability-parents reported that the leaflet was clearly designed. (3) Decision aid-parents commented that the leaflet provided clarification around recognition of serious symptoms and when and where to seek appropriate care.Conclusions: Our leaflet provided parents with guidance on decision making and risk assessment of ill children during COVID-19 lockdown. Parents found it helpful; it increased their confidence and positively changed their health-seeking behaviors. Providing parents with targeted information to recognize serious illness in children at home could potentially foster self-care and safely maintain a reduction in pediatric emergency attendances for self-limiting illnesses.